(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Article 45 of Constitution of India as a part of directive principles of State policy, directs the state to make the provisions within a period of ten years from the commencement of this constitution for free and compulsory education for all children till the completion of their 14 years age. The 86th amendment in Article 21A in 2002 says that the State Shall provide free and compulsory education to all children aged 6-14 years; this way it makes education a fundamental right that’s meaning it is enforceable by law. The RTE Act, 2009 inducts the entitlement to free and compulsory elementary education, access to school and barrier free access for all children including Divyang children. Section 3(2) of the RTE Act lays emphasis on the elementary education of all differently able children. The Right of Persons with Disabilities (RPWD) Act 2016 came into the force on 19th April 2017 which repealed the PWD Act 1995. Section 16 of RPWD Act 2016 strongly enforced the provisions for learning of Divyangjan students as mentioned in the section 2(d) and 2(ee) of RTE Act 2009. In the year 2022 the survey conducted in Samgra Shiksha Programme by Govt. of India, it shows surprising figure that total enrollment at Class 1-12 level is only 0.70% of divyangjan students in Uttar Pradesh, which is critical in spite of using heavy expenditure and continuous monitoring at primary level education in Uttar Pradesh. The present study aims to find the weakness and challenges stable in primary schools providing education to Divyangjana students at primary level. For this the researcher has selected the primary schools located in the districts of Meerut commissionaire of Uttar Pradesh (India). The researcher used a self made questionnaire scale for collection the data regarding available resources, facilities, schemes and other provisions in the schools. The results showed the surprising outputs.